The Change of Name of Character in the Legend of Nyi Roro Kidul as a Trace of the Spread of Islam at Palabuhanratu Sukabumi Regency - Shobah, Fitri Nurul; Durachman, Memen; Harini, Yostiani Noor Asmi (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
The phenomenon of name changes can be found among public figures and the general public who decide to embrace Islam and change or choose Islamic names as evidence of the spread of Islam. Not only in real life, name changes also occur in legends, one of which is in the legend of Nyi Roro Kidul in Palabuhanratu, Sukabumi Regency. The purpose of this study is to show the pattern of name changes that can be used as an indicator of the spread of Islam in Palabuhanratu, Sukabumi Regency. The method used in this study is a qualitative method, with observation and interview techniques. The results of this study found five figures who experienced name changes as part of the spread of Islam in Palabuhanratu, Sukabumi Regency. This change can be interpreted as a form of cleansing or self-purification. She returned to being a holy or virgin figure, as per the concept tazqiyah in Islam, namely self-purification through a spiritual journey which ultimately took her to a higher level, both in the spiritual aspect and her status as Queen of the South Coast.